APPLICATION OF LINEAR AND AREA PARAMETERS IN THE HIGH COURSE OF THE SANTO ANTÔNIO HYDROGRAPHIC BASIN, MARANHÃO - Maciel, Dayana Serra; Silva, Quésia Duarte da; França, Danyella Vale Barros (Geosaberes; Vol 12 (2021), 2021)
The hydrographic basin is an important instrument for the planning and management of water resources, being defined as an area bounded by water divisions formed by a main river and its tributaries. This work aims to understand the physiography and hydrology of the high course of the hydrographic basin of Santo Antônio, Ilha do Maranhão through morphometric analysis. This research has a theoretical and empirical character and in order to reach the objective, a bibliographic, cartographic and morphometric data survey was carried out, thematic maps were elaborated and field work was carried out. The morphometric data collected in the study area took into account the linear and sandy analysis and through the results achieved it was possible to better interpret the physiography and the hydrological behavior of the high course. These data can serve as a basis for monitoring this basin and analyzing areas subject to floods.